Effects of Sodium Thiosulfate During Resuscitation From Trauma-and-Hemorrhage in Cystathionine Gamma Lyase (CSE) Knockout Mice. Issue 1 (23rd January 2022) - Gröger, Michael; Hogg, Melanie; Abdelsalam, Essam; Kress, Sandra; Hoffmann, Andrea; Stahl, Bettina; Saub, Veronique; Denoix, Nicole; McCook, Oscar; Calzia, Enrico; Wolfschmitt, Eva-Maria; Wachter, Ulrich; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Sodium thiosulfate (Na2 S2 O3 ) is a clinically established drug with antioxidant and sulphide-releasing properties. Na2 S2 O3 mediated neuro- and cardioprotective effects in ischemia/reperfusion models and anti-inflammatory effects in LPS-induced acute lung injury. Moreover, Na2 S2 O3 improved lung function during resuscitation from hemorrhagic shock in swine with pre-existing atherosclerosis, characterized by decreased expression of cystathionine γ-lyase (CSE), a major source of hydrogen sulfide (H2 S) synthesis in the vasculature. Based on these findings, we investigated the effects of Na2 S2 O3 administration during resuscitation from trauma-and-hemorrhage in mice under conditions of whole body CSE deficit. Methods: After blast wave-induced blunt chest trauma and surgical instrumentation, CSE knockout (CSE −/− ) mice underwent 1 h of hemorrhagic shock (MAP 35 ± 5 mm Hg). At the beginning of resuscitation comprising retransfusion, norepinephrine support and lung-protective mechanical ventilation, animals received either i.v. Na2 S2 O3 (0.45 mg g −1, n = 12) or vehicle (saline, n = 13). Hemodynamics, acid–base status, metabolism using stable isotopes, and visceral organ function were assessed. Blood and organs were collected for analysis of cytokines, mitochondrial respiratory capacity, and immunoblotting. Results: Na2 S2 O3 treatment improved arterial paO2 ( P = 0.03) coinciding with higher lung tissue glucocorticoid receptor expression. Norepinephrine requirements were lower in the Na2 S2 O3 group ( P < 0.05), which was associated with lower endogenous glucose production and higher urine output. Na2 S2 O3 significantly increased renal tissue IκBα and heme oxygenase-1 expression, whereas it lowered kidney IL-6 and MCP-1 levels. Conclusion: Na2 S2 O3 exerted beneficial effects during resuscitation of murine trauma-and-hemorrhage in CSE −/− mice, confirming and extending the previously described organ-protective and anti-inflammatory properties of Na2 S2 O3 . The findings make Na2 S2 O3 a potentially promising therapeutic option in the context of impaired CSE activity and/or reduced endogenous H2 S availability.